Implementation of the Independent Curriculum in Islamic Religious Education Subjects at SMK Citra Medika, Magelang City - Riyanto, Dodi; Tohirin, M.; Baihaqi, Akhmad (Prosiding University Research Colloquium, 2023)
This study discusses the Implementation of the Independent Curriculum in Islamic Religious Education Subjects at PK Citra Medika Vocational High School, Magelang City with the research objectives namely: (1) To find out how the implementation of the Independent Curriculum in Islamic Religious Education subjects at SMK Citra Medika Excellence Center, Magelang City. (2) To find out the supporting and inhibiting factors for the implementation of the Independent Curriculum in the subject of Islamic Religious Education at the Center for Excellence Citra Medika Vocational High School, Magelang City. The type of research used is field research. This research is a qualitative research using a phenomenological approach. Data collection techniques are carried out through observation, interviews, and documentation. Furthermore, data analysis was carried out by data reduction, data presentation, and conclusions. The data validity technique uses the credibility, transferability, dependability, and confirmability tests. The results of the research show that (1) Planning, implementation, and evaluation in PAI learning are in accordance with the principles of implementing the Independent Curriculum. In the implementation of the Pancasila Student Profile Strengthening Project (P5) at PK Citra Medika Vocational School, it contains the values of Islamic Religious Education (PAI) which can be an optimal means of encouraging students to become lifelong learners who are competent, have character, and behave in accordance with these values. Pancasila. This illustrates that the implementation of the Independent Curriculum in PAI subjects has been going well. (2) The supporting factors in supporting the success of PAI learning are the existence of the Rohis extracurricular program. In implementing the Independent Curriculum there are obstacles faced by PAI teachers, namely the lack of availability of infrastructure that supports the PAI learning process according to the procedures in the Independent Curriculum.